2010
DOI: 10.1109/icbbe.2010.5516138
|View full text |Cite
|
Sign up to set email alerts
|

Dispersibility of SZP Antimicrobial Agents in Silicone Denture Soft Lining Materials and Their Effect on Operational Performance

Abstract: The purpose of this study is to investigate the dispersibility of silver-zirconium phosphate (SZP) nanoinorganic antimicrobial agent in silicone denture soft lining materials and the effect of adding the agent on operational performances. SZP was added using the method of high shear emulsification dispersion. The mass percent of antimicrobial agent was 2%, 5%, and 10%. Silicone soft lining materials without antimicrobial agent served as controls. Dispersibility of SZP in silicone soft lining materials was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Transmission electron microscopy (TEM) analysis and atomic adsorption spectroscopy revealed that silver nanoparticles are compatible with the acrylic formulation and remain well-dispersed in the final material. Silver nanoparticles have no detrimental effect on the photopolymerization kinetics and the incorporation of nanoparticles was found to reduce the gloss of ultraviolet-cured coatings [61] .…”
Section: Nanoparticles In Dental Applicationsmentioning
confidence: 97%
“…Transmission electron microscopy (TEM) analysis and atomic adsorption spectroscopy revealed that silver nanoparticles are compatible with the acrylic formulation and remain well-dispersed in the final material. Silver nanoparticles have no detrimental effect on the photopolymerization kinetics and the incorporation of nanoparticles was found to reduce the gloss of ultraviolet-cured coatings [61] .…”
Section: Nanoparticles In Dental Applicationsmentioning
confidence: 97%
“…Transmission electron microscopy (TEM) analysis and atomic adsorption spectroscopy revealed that silver nanoparticles are compatible with the acrylic formulation and remain well-dispersed in the final material. Silver nanoparticles have no detrimental effect on the photopolymerization kinetics and the incorporation of nanoparticles was found to reduce the gloss of ultraviolet-cured coatings[70].…”
Section: Nano-structured Materials and Their Applicationsmentioning
confidence: 97%